CDK5RAP2 gene and tau pathophysiology in late‐onset sporadic Alzheimer's disease. Issue 6 (19th January 2018) - Miron, Justin; Picard, Cynthia; Nilsson, Nathalie; Frappier, Josée; Dea, Doris; Théroux, Louise; ,; ,; Poirier, Judes
Abstract: Introduction: Because currently known Alzheimer's disease (AD) single‐nucleotide polymorphisms only account for a small fraction of the genetic variance in this disease, there is a need to identify new variants associated with AD. Methods: Our team performed a genome‐wide association study in the Quebec Founder Population isolate to identify novel protective or risk genetic factors for late‐onset sporadic AD and examined the impact of these variants on gene expression and AD pathology. Results: The rs10984186 variant is associated with an increased risk of developing AD and with a higher CDK5RAP2 mRNA prevalence in the hippocampus. On the other hand, the rs4837766 variant, which is among the best cis‐expression quantitative trait loci in the CDK5RAP2 gene, is associated with lower mild cognitive impairment/AD risk and conversion rate. Discussion: The rs10984186 risk and rs4837766 protective polymorphic variants of the CDK5RAP2 gene might act as potent genetic modifiers for AD risk and/or conversion by modulating the expression of this gene.